ABC of interventional cardiology - Grech, Ever D. (ABC series, 2004)
Coronary artery disease causes severe disability and more death than any other disease in affluent societies. Medical conditions associated with this disease are angina, ischaemia, unstable angina, myocardial infarction, arrhythmias, heart failure, and sudden death.In recent years, interventional cardiology, particularly percutaneous coronary intervention, has progressed dramatically and undergone incredible evolution. In many countries, numbers of percutaneous coronary procedures now equal or exceed bypass surgery.. Although coronary intervention has held centre stage, major inroads in non-coronary percutaneous intervention have been made. Much of the breathtaking momentum seen in interventional cardiology in recent years has been captured in this highly informative and well illustrated ABC of Interventional Cardiology. It will help the reader to make decisions on cardiac diagnosis and appropriate care, and to advise patients on the benefits that percutaneous intervention can offer. Chapters include: Pathophysiology and investigation of coronary artery disease; Percutaneous coronary intervention; Chronic stable angina: treatment options; Acute coronary syndrome; Percutaneous coronary intervention: cardiogenic shock; Interventional pharmacotherapy; Non-coronary percutaneous intervention; New developments in percutaneous coronary intervention; Percutaneous interventional electrophysiology; Implantable devices for treating tachyarrhythmias; Interventional paediatric cardiology.